1999
DOI: 10.1073/pnas.96.21.11804
|View full text |Cite
|
Sign up to set email alerts
|

Double duplex invasion by peptide nucleic acid: A general principle for sequence-specific targeting of double-stranded DNA

Abstract: Pseudocomplementary PNAs containing diaminopurine⅐thiouracil base pairs have been prepared and are shown to bind with high specificity and efficiency to complementary targets in doublestranded DNA by a mechanism termed ''double duplex invasion'' in which the duplex is unwound and both DNA strands are targeted simultaneously, each by one of the two pseudocomplementary peptide nucleic acids (PNAs). On the basis of our results we predict that (for decameric targets) more than 80% of all sequences can be targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
248
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(261 citation statements)
references
References 26 publications
12
248
0
Order By: Relevance
“…It must be noted that modified nucleobases termed A* and T* were used instead of A and T. A* and T* recognize T and A respectively, but A* and T* do not recognize each other (See Figure 11a for a schematic of the base pairing and Figure 11b for the structure of the combinatorial library of cyclen derivatives containing PNA oligomers). 89 Base pairing among PNA mixtures present in the library can thus be suppressed by using A* and T*. These findings are very promising and show that a library of PNAs can be used not only to recognise specific DNA or RNA strands but also to selectively bind a target protein.…”
Section: Metal-containing Pnas As Artificial Nucleasesmentioning
confidence: 84%
“…It must be noted that modified nucleobases termed A* and T* were used instead of A and T. A* and T* recognize T and A respectively, but A* and T* do not recognize each other (See Figure 11a for a schematic of the base pairing and Figure 11b for the structure of the combinatorial library of cyclen derivatives containing PNA oligomers). 89 Base pairing among PNA mixtures present in the library can thus be suppressed by using A* and T*. These findings are very promising and show that a library of PNAs can be used not only to recognise specific DNA or RNA strands but also to selectively bind a target protein.…”
Section: Metal-containing Pnas As Artificial Nucleasesmentioning
confidence: 84%
“…Strand invasion by PNAs has been demonstrated on supercoiled DNA using mixed sequences 37 and on relaxed dsDNA with polypyrimidine PNAs targeting polypurine motifs. [38][39][40] Moreover, although in vivo, there is little evidence for antigene activity of PNAs, several groups have reported that PNAs can induce downregulation of target mRNA and have suggested either an antigene mechanism by interaction with target DNA, which inhibits the transcription machinery, or that PNA interaction with mRNA targets triggers its degradation through a hypothetical mechanism. [11][12][13][14] However, the PNAs used in these studies do not target homo-purine motifs, and would not be able to form a stable complex with DNA in order to block RNA polymerase.…”
Section: Resultsmentioning
confidence: 99%
“…16,56,57 This cutter is composed of two pcPNAs [58][59][60][61] and Ce(IV)/EDTA ( Figure 11). The pcPNAs used are designed to be laterally shifted to one another by five nucleobases.…”
Section: Site-selective Scission Of Double-stranded Dna By the Combinmentioning
confidence: 99%
“…The site specificity and target site of this artificial DNA cutter can be almost freely modulated; therefore, this cutter should be useful in developing new biotechnology. For instance, viruses with single-stranded genomes can be manipulated to produce 59 Lohse et al 60 and Komiyama et al 61 ).…”
Section: Site-selective Scission Of Double-stranded Dna By the Combinmentioning
confidence: 99%